Preface - Herawan, Tutut (Journal of Information Systems Research and Practice, 2024)
The Volume 2 Issue 5 of JISRP: SUPPLEMENTARY ISSUE on Soft Computing and Data Mining (SCDM) availables online on December 14th, 2024. The issue has been available online for accepted papers (uncorrected proofs).